2008
DOI: 10.1186/1471-2474-9-120
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine increases hyaluronic acid production in human osteoarthritic synovium explants

Abstract: Background: Glucosamine (GlcN) used by patients with osteoarthritis was demonstrated to reduce pain, but the working mechanism is still not clear. Viscosupplementation with hyaluronic acid (HA) is also described to reduce pain in osteoarthritis. The synthesis of HA requires GlcN as one of its main building blocks. We therefore hypothesized that addition of GlcN might increase HA production by synovium tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…In this study, both passive and active range of motion of the knee improved significantly in participants who consumed MFGM1glucosamine, and there was a significant group-by-time interaction. Glucosamine has been reported to have a positive effect on the synthesis and degradation of cartilage (14-17) and a stimulatory effect on production of hyaluronic acid in the synovium (18). In a study performed in young athletes, 4 wk of glucosamine consumption improved the passive range of motion in injured knees (19).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both passive and active range of motion of the knee improved significantly in participants who consumed MFGM1glucosamine, and there was a significant group-by-time interaction. Glucosamine has been reported to have a positive effect on the synthesis and degradation of cartilage (14-17) and a stimulatory effect on production of hyaluronic acid in the synovium (18). In a study performed in young athletes, 4 wk of glucosamine consumption improved the passive range of motion in injured knees (19).…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors include platelet‐derived growth factor, transforming growth factor‐β, and insulin‐like growth factor, which have been found in vitro to promote the expression of type 1 and 3 collagen in tenocytes [18]. In additional in vitro studies, human osteoarthritic synovial tissue exposed to glucosamine and glucose produced increased levels of hyaluronic acid production [19].…”
Section: Regenerative Agents: Evidence Basementioning
confidence: 99%
“…mine, thereby decreasing infl ammation, and become a viable option in prevention and rehabilitation of joint degenerative disease [ 3 ] . Moreover, it has been demonstrated that glucosamine has an anti-infl ammatory eff ect via the reduction of nuclear factor kappa beta induced by interleukin-1 (IL-1) in animal models [ 4 ] .…”
Section: Comparative Fasting Bioavailability and Pharmacokinetic Propmentioning
confidence: 99%